CASE REPORT: COEXISTENCE OF CELIAC DISEASE AND MULTIPLE MYELOMA - Filiz YAVASOGLU (Elsevier, 2021)
Objective: Celiac disease is a systemic disease in which the natural and adaptive immune system is affected by the effect of gluten exposure and environmental factors in individuals with genetic predisposition. Multiple myeloma; is characterized by an increase in clonal plasma cells. It is the most common hematological malignancy after lymphomas.We aimed to present a case siagnosed with celiac disease and multipl myeloma Case report: A 56-year-old female patient with a diagnosis of asthma and celiac disease for 1 year was referred to the Hematology department because her refractory anemia. Serum IgA level of the patient was 4490 mg/dl without renal failure and hypercalcemia.bone marrow biopsy compatible with myeloma. The patient received 6 cycles of bortezomib, cyclophosphamide, and dexamethasone and 3 cycles lenalidomid dexametazon chemotherapy.After chemotherapy, Autologous stem cell transplantation was performed. Conclusion: Celiac disease is an autoimmune disease, characterized by inflammation and villus atrophy in the small intestine mucosa as a result of sensitivity to gluten, resulting in malabsorption. The incidence of lymphoma and gastrointestinal system malignancy is increased in individuals with celiac disease. Multiple myeloma may also be accompanied by autoimmune diseases such as ankylosing spondylitis, scleroderma, and sjögren's syndrome. Coexistence of multiple myeloma and celiac disease is rare.